Supplementary household water sources to augment potable municipal supply in South Africa - Du Plessis, Kobus; Nel, Nicole; Jacobs, Heinz; Loubser, Carlo (Water S. A., 2017)
This paper addresses on-site supplementary household water sources with a focus on groundwater abstraction, rainwater harvesting and greywater reuse as available non-potable water sources to residential consumers. An end-use model is presented and used to assess the theoretical impact of household water sources on potable water demand in formal residential areas. Reliable potable municipal supply to urban consumers via the water distribution system is typically linked to relatively low uptake of household water sources. However, stringent water restrictions in some large South African cities that prohibit outdoor use, and reports of intermittent water supply, have led to increased uptake of household sources in South Africa. This paper describes the legal position regarding such sources in South Africa, and describes an end-use model to assess the theoretical impact on water demand in formal residential areas. The model provides valuable strategic direction and indicates a significant theoretical reduction in potable municipal water demand of between 55% and 69% for relatively large properties when household sources are maximally utilised (when compared to exclusive unrestricted municipal use as a baseline). This load reduction on piped reticulation systems could be an advantage in order to augment municipal supply, but water service planning and demand management are complicated by the introduction, and possible future decommissioning, of any household water source. The extent of both positive and negative impacts of household water sources requires further research.